Clustered Regularly Interspaced short palindromic repeats‐Based Microfluidic System in Infectious Diseases Diagnosis: Current Status, Challenges, and Perspectives. Issue 34 (18th October 2022) - Xie, Yi; Li, Huimin; Chen, Fumin; Udayakumar, Srisruthi; Arora, Khyati; Chen, Hui; Lan, Yang; Hu, Qinqin; Zhou, Xiaonong; Guo, Xiaokui; Xiu, Leshan; Yin, Kun
Abstract: Mitigating the spread of global infectious diseases requires rapid and accurate diagnostic tools. Conventional diagnostic techniques for infectious diseases typically require sophisticated equipment and are time consuming. Emerging clustered regularly interspaced short palindromic repeats (CRISPR)/CRISPR‐associated proteins (Cas) detection systems have shown remarkable potential as next‐generation diagnostic tools to achieve rapid, sensitive, specific, and field‐deployable diagnoses of infectious diseases, based on state‐of‐the‐art microfluidic platforms. Therefore, a review of recent advances in CRISPR‐based microfluidic systems for infectious diseases diagnosis is urgently required. This review highlights the mechanisms of CRISPR/Cas biosensing and cutting‐edge microfluidic devices including paper, digital, and integrated wearable platforms. Strategies to simplify sample pretreatment, improve diagnostic performance, and achieve integrated detection are discussed. Current challenges and future perspectives contributing to the development of more effective CRISPR‐based microfluidic diagnostic systems are also proposed. Abstract : The CRISPR/Cas detection systems that are armed with state‐of‐the‐art microfluidic platforms have shown remarkable potential as next‐generation diagnostic tools. In this review, CRISPR‐based microfluidic systems for infectious diseases diagnosis, including the mechanisms of CRISPR/Cas biosensing and the cutting‐edge microfluidic devices are systematically summarized. Additionally, current challenges and future perspectives are discussed to develop more effective CRISPR‐based microfluidic diagnostic systems.